Phytochemical and Therapeutic Evaluation of an Ethnomedicinal Plant of Tripura: Mimosa pudica - De, Biplab; Chakraborty, Avijit; Majumder, Tandrima; Chanda, Shilpi; Behari Goswami, Binoy (Asian Journal of Chemistry, 2010)
The methanolic extract of whole plant of Mimosa pudica, an ethnomedicinal plant of Tripura, India showed spermicidal and anticoagulant activity and separated compounds were also evaluated. The structure of the most active component is reported.